Quarter-Wave Stepped-Impedance Resonator Filters with Quadruplet and Canonical Form Responses - Lu, Jhe-Ching; Chang, Chi-Yang (My University, 2008)
In this paper, compact microstrip quarter-wave stepped-impedance resonator (SIR) bandpass filters with quadruplet and canonical form responses are proposed. The proposed quadruplet filter can be designed to have a pair of transmission zeros to achieve sharp selectivity. In addition, by applying an extra source-load coupling, two additional transmission zeros on both side of passband are created to further enhance the selectivity. Because the quarter-wave SIRs are adopted, the circuit size of the filters can be largely reduced and the upper stopband can be extended. Two generalized Chebyshev filters corresponding to quadruplet and canonical form coupling schemes are fabricated. Simulated and measured results are matched very well.